(untitled) (CAHIERS MAGELLANES-NS, 2024)
The utilization of biological and environmentally friendly synthesis processes presents a promising alternative to conventional physico-chemical methods. This study explores the potential of leveraging biological entities such as plants, fungi, and bacteria in the synthesis of iron nanoparticles, highlighting the efficacy of green techniques in nanoparticle production. Specifically, this study demonstrate the use of Vernonia cineria leaf extract for the generation of iron nanoparticles, showcasing its multifunctional role as surface stabilizers, capping agents, and reducing agents. Iron nano particles from V. cineria leaf extract characterization by UV visible spectroscopy, FTIR, XRD, SEM and EDAX. Antibacterial and antifungal assays demonstrated the efficient activity of iron nanoparticles against pathogens, indicating potential biomedical applications. The photodegradation experiments highlighted the photocatalytic potential of iron nanoparticles, with degradation efficiency improving over time. The substantial percentage of degradation achieved within the first 120 minutes underscores the effectiveness of the degradation process under the experimental conditions. Future research should further explore the potential applications of iron nanoparticles synthesized from V. cineria extract and investigate their environmental and biomedical implications.